Water pollution studies in the rivers of the Edirne Region-Turkey - YARCI, CELAL (TAYLOR & FRANCIS INC, 2009)
Physico-chemical parameters of Tunca, Merich, Arda and Ergene rivers, in the Edirne region of Turkey, were investigated. Studies were carried out during 1998-2004 and the data obtained were compared with EU threshold levels. The results showed that the total concentrations of P, Pb, Cu, Ni, Mn and Co were higher than these threshold levels. There is an urgent need for Turkey to limit water pollution from a wide range of dangerous substances, particularly at a time when it is being considered as an EU candidate. Turkey will be required to achieve a satisfactory status in its waters by 2015, in particular in the waters of the rivers investigated in this paper that border Bulgaria and Greece. Levels of pollutants which pose a significant risk to the aquatic environment need to be monitored and strictly controlled.
Keywords: Tunca; Merich; Arda; Ergene; physico-chemical; trace metals; HEAVY-METAL POLLUTION; SEDIMENTS; CONTAMINATION